The effect of detailed analysis as feedback on the performance of elite squash players - Murray, S. R.; Maylor, D.; Hughes, M. D.
It appears that both groups in this reacted positively to the feedback provided. The sub-elite group showed a greater change in performance ,but, as argued before the minimal elite change had as great an effect on match results. However, in order to gauge the exact effect of feedback alone, complete control conditions would be needed in order to minimise the effect of other external variables. The sub-elite performers displayed more significant improvements (p<0.05) in specific shot types. Arguably, this is representative of the relatively easy task of improving performance when at a lower level of competence (Thomas and Thomas, 1994). It is clear that the intrapersonal nature of the elite group had a impact on the study. This may need to be noted by coaches working with such groups in the future. In this study the psychological states of the subjects also had effect on their performance, be it positive or negative, and evidently further research into this area would improve the status and understanding of the competitive squash coach. In this study quantitative feedback induced a significant temporal transition in performance levels of both groups. The findings were consistent with earlier research on the effect of quantitative feedback (Schmidt, 1982; Salmoni, Schmidt, and Walter, 1984; Magill, 1993; Franks, 1997a).